Blending Research-Based Practices and Practice-Embedded Research: Project Excite Closes Achievement and Excellence Gaps for Underrepresented Gifted Minority Students. (July 2017) - Olszewski-Kubilius, Paula; Steenbergen-Hu, Saiying
In this article, we advocate for a new movement in education, particularly an approach emphasizing blending research-based practice with practice-embedded research. We do so by describing and discussing Project Excite, a working example that demonstrates such a model in the context of gifted education. We first trace the history, the impetus, and key design elements of Project Excite, a front-loading intervention aiming to develop the potential of underrepresented students for advanced science, technology, engineering, and mathematics learning from early grades. We review a line of past research and key findings on Project Excite over its 14-year journey. We then discuss the implication of Project Excite for gifted programming in gifted education. Last, we pinpoint some questions to inspire future research and practice.